2021
DOI: 10.9734/jpri/2021/v33i39a32137
|View full text |Cite
|
Sign up to set email alerts
|

A Review Article on the Relation between Anxiety and Depression

Abstract: Anxiety depression is the commonest phenomena in preponderant population. Many individuals might have experience it and still not know, very often in a state of constant denial and negligence with the fact knowingly. The causes can vary from psychological, physiological and traumatic past experiences. This article incorporate studies of anxietydepression and their relationship and causes. Anxiety depression are the most common psychological disorder. Their relationship is very baffling, their symptoms overlaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The study findings revealed a positive correlation between anxiety and depression, consistent with previous research, indicating a significant overlap between these two emotional states and emotional disorders. 63 A significant negative correlation has been reported between psychological stress and active coping style, and a significant positive correlation was documented between psychological stress and passive coping style among obstetric nurses. 64 Similarly, anxiety and depression have been found to have a significant negative correlation with active coping style and a significant positive correlation with passive coping style.…”
Section: Discussionmentioning
confidence: 98%
“…The study findings revealed a positive correlation between anxiety and depression, consistent with previous research, indicating a significant overlap between these two emotional states and emotional disorders. 63 A significant negative correlation has been reported between psychological stress and active coping style, and a significant positive correlation was documented between psychological stress and passive coping style among obstetric nurses. 64 Similarly, anxiety and depression have been found to have a significant negative correlation with active coping style and a significant positive correlation with passive coping style.…”
Section: Discussionmentioning
confidence: 98%
“…Of course, both the mother and the foetus suffer negative repercussions from severe anaemia. (26)(27)(28)(29)(30) Additionally, there is proof that less severe anaemia is linked to unsuccessful pregnancies. There is still no clear explanation for this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The CPPs are joined to the posterior medullary velum in the fourth ventricle. (25)(26)(27)(28)(29)(30) Due to the pedicular connection, which allows for the free movement of the tumours inside the ventricles, there can occasionally be an acute constriction of the ventricles caused by gravity, leading to bobble head doll syndrome. In our case, the tumour also possessed a pedicular attachment that emerged from the temporal horn's choroid plexus, with the anterior choroidal artery serving as its vascular supply.…”
Section: Discussion:-mentioning
confidence: 99%